Investigation of different compressor speeds to improve the performance of residential air conditioning system using hybrid nanolubricant - S., Safril; Wan Azmi, Wan Hamzah; Mustakim, . (Faculty Mechanical Engineering, UMP, 2025)
Nanoparticles dispersed into lubricants improve the performance of residential air conditioning (RAC) systems. Due to the addictive nature of nanoparticles, friction losses are reduced, and heat transfer is enhanced, leading to a significant increase in the overall efficiency of the RAC system. This study aimed to investigate different compressor speeds utilising hybrid nanolubricant to improve the performance of RAC. A two-step method was used to prepare TiO2 and SiO2 nanoparticles dispersed into polyvinyl ether (PVE) lubricant at a volume concentration of 0.008%. R32 refrigerant was formulated with PVE lubricant at a refrigerant charge of 360 g and compressor speeds of 2520, 2760, and 3000 rpm. The dispersion of both nanoparticles into PVE lubricant at a binary ratio of 50:50 showed excellent stability. The results of the experimental study showed that the coefficient of performance (COP) at each compressor speed of 2520, 2760, and 3000 rpm increased by 8.04%, 4.51%, and 2.46%, respectively. Then, the compressor work decreased by 8.05%, 6.30%, and 4.53%, respectively, decreasing maximum power consumption by 3.56% at a compressor speed of 2520 rpm. Increasing COP at low speeds has implications for the compressor work, which causes the mass flow rate to decrease. At the same time, the refrigerant effect increases, and finally, the COP increases. It is concluded that utilising hybrid nanolubricant in the refrigeration system can improve the overall performance of RAC.